Полиморфная структура отдельных наночастиц YSZ и Al2O3 - Шевченко В. Я.; Хасанов О. Л. Олег Леонидович; Lee J. Y.; Похолков Ю. П. Юрий Петрович; Двилис Э. С. Эдгар Сергеевич; Мадисон А. Е. (2003, 2003)
В фонде НТБ ТПУ отсутствует